Study Effect of Adding Expanded Polystyrene as A Percentage of Cement Weight on The Properties of Concrete Mixture in Construction (Sebha University Conference Proceedings, 2025)
In this research, a study was conducted to produce a type of lightweight concrete to try to use it in building units, where different proportions of polystyrene granules were used, and this material was tested because of its low density compared to other types of aggregates. The addition of polystyrene (waste) to the components of concrete has an effect on the density, which is related to all other mechanical and physical properties of concrete. The study focused on the use of polystyrene granules in concrete mixtures as a percentage of the weight of cement at (0%, 2%, 3.5%, 5%) to obtain lightweight concrete. From the results of the pressure tests, it became clear that the highest compressive strength was recorded in the addition of polystyrene at a rate of 2% with a value of 18.5MPa at 28 days, where it decreased from the reference mixture by 14.5% and the lowest at a rate of 5% with a compressive strength of 4MPa and decreased from the reference by 29%. In tensile strength, the highest was 2% with a tensile strength of 1.99MPa and recorded a decrease compared to the reference by 1.56% and the lowest in the tensile strength at 5% was 0.78MPa and the reference reduction was 2.77%. In terms of density results, the highest additions were at 2% with a value of 2247.4Kg/m3 and the lowest was at 5% with a density of 17742Kg/m3, and the reference absorption rate was 1.2%, and for 2% polystyrene the absorption rate was 4%, and for 5% polystyrene the absorption was 6.2%. Through experiments, the density decreases with increasing polystyrene percentage as a percentage of cement, although the compressive strength decreases as the percentage of polystyrene increases in concrete mixtures, it can be used in non-load-bearing structural elements such as concrete blocks, the possibility of using harmful industrial waste from polystyrene after recycling it in useful fields such as manufacturing lightweight concrete, and this contributes to preserving the environment.